2017
DOI: 10.1016/j.fsigss.2017.09.054
|View full text |Cite
|
Sign up to set email alerts
|

Establishing the limit of detection of massively parallel sequencing using laser micro-dissected cells

Abstract: Massively parallel sequencing is fast emerging as an increasingly useful tool for forensic science. As part of our ongoing validation of this technology we wanted to both ensure compatibility of the technology with laser microdissected (LMD) cells and use the LMD to explore the minimal and optimal numbers of cells required to generate informative profiles. To do this we used the ForenSeq™ DNA Signature Prep Kit and a MiSeq FGx™ Sequencer. In this paper we describe the modifications made to our one step DNA ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…Although the recommended input is 1 ng, several studies have found the sensitivity of the kit to be lower than the 1 ng input recommended. For example, Jäger et al (2017) found full STR profiles could be generated from 31.25 pg input DNA using DPMA and DPMB, Guo et al (2017) obtained full STR profiles from 100 pg input DNA using DPMA, and Nancollis, England, and Harbison (2017) produced full STR profiles from 100 laser micro-dissected epithelial cells and 200 spermatozoa using DPMB.…”
Section: Dna Extraction and Quantificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the recommended input is 1 ng, several studies have found the sensitivity of the kit to be lower than the 1 ng input recommended. For example, Jäger et al (2017) found full STR profiles could be generated from 31.25 pg input DNA using DPMA and DPMB, Guo et al (2017) obtained full STR profiles from 100 pg input DNA using DPMA, and Nancollis, England, and Harbison (2017) produced full STR profiles from 100 laser micro-dissected epithelial cells and 200 spermatozoa using DPMB.…”
Section: Dna Extraction and Quantificationmentioning
confidence: 99%
“…In the ForenSeq™ method, a 1:1 ratio of beads to library volume is used, selecting for fragments greater than 200 bp. If very few larger library fragments are present because the input DNA was degraded or low in quantity, then adapter dimers remain in the solution after purification (Jäger et al, 2017;Nancollis et al, 2017), and interfere with cluster formation on the flow cell.…”
Section: Purify Librariesmentioning
confidence: 99%